Promoción y prevención en salud oral asistida virtualmente en la población vulnerable de estudiantes de segundo grado de la institución educativa santos apóstoles de Cúcuta - Niño Balaguera, Slendy Viviana; Bermon Martínez, Karen Marbell (Universidad Antonio Nariño, 2022)
Levels of knowledge about oral hygiene habits in parents and children prior to educational intervention had poor results, released that there is a large misinformation about oral hygiene habits, after which, this level of knowledge increased significantly, thus determining that educational interventions are of vital importance for parents and schoolchildren to have more favorable behaviors and this will help to maintain good oral health.